L’évolution de la professionnalité des inspecteurs pédagogiques régionaux d’éducation physique et sportive dans les années 1980 et 1990 - Clémence Lebossé (Éducation et Socialisation)
Based on an analysis of archival sources, printed sources and oral sources, this contribution aims to bring to light the extension of the managerial domain to the sector of the pedagogical Inspection in charge of physical education (PE) in the 1980s and 1990s. Under the joint influence of the attachment of this teaching discipline to the National Education and the development of the New Public Management, the professionalism of these PE actors evolved in response to the new evaluation and performance requirements of the French education system. The model of the inspector in the field, sanctioning the pedagogical acts of PE teachers, is being abandoned in favor of the model of the expert manager and multi-tasker who is required to master new audit, evaluation and control techniques.